Interpreting the Biblical Words for the Self - Clark, David K. (Journal of psychology and theology, 1990)
Biblical language describing the sinful dimensions of human personality creates many confusions. Some have thought that Jesus calls his followers to deny their very personhood (Luke 9:23). In this view, “deny yourself” requires that disciples reject entirely any notion of a positive self-concept. But biblical words like self, flesh, and old self refer not to things, but to qualities. They highlight the selfish dimensions of fallen human personalities. Their referent is not essential human personhood. By clarifying language, we suggest that humanness per se can be good, as it is created by God, even though it is entangled in sin in its present fallen state. This implies that “deny yourself” is consistent with “have a positive self-concept.”